Gender parity and inorganic fertilizer technology adoption in farm households: Evidence from Niger - Tankari, Mahamadou Roufahi (Wageningen Academic Publishers, 2018)
This study seeks to address the gap in understanding the role of gender parity in inorganic fertiliser technology adoption in Niger. The empirical strategy is firstly based on the calculation of the household parity indicator following the Women’s Empowerment in Agriculture Index (WEAI) approach and, secondly, it relies on binary regressions. It appears that gender parity in the household affects negatively the adoption of inorganic fertiliser. Thus, accompanying measures are needed to correct this negative effect of gender parity on the fertiliser technology adoption. The study also highlights a number of determinants of gender parity and adoption of fertilisers in agricultural households that can serve policy design.